1998
DOI: 10.1016/s0165-5728(97)00187-2
|View full text |Cite
|
Sign up to set email alerts
|

The roles of Fas, Fas ligand and Bcl-2 in T cell apoptosis in the central nervous system in experimental autoimmune encephalomyelitis

Abstract: The selective apoptotic elimination of autoreactive T cells in the central nervous system (CNS) contributes to the resolution of inflammation and the spontaneous clinical recovery from experimental autoimmune encephalomyelitis (EAE). To assess the molecular mechanisms involved in this process, we used three-colour flow cytometry to examine the expression of apoptosis-regulating proteins by inflammatory cells isolated from the spinal cords of Lewis rats immunized with myelin basic protein (MBP) and complete Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 47 publications
5
43
0
Order By: Relevance
“…In the present study we have shown that B cells expressing CD95 or CD95L in the CNS are much more vulnerable to apoptosis than B cells not expressing these proteins. This strongly suggests that B cell apoptosis in the CNS in EAE is mediated by the interaction of CD95L and CD95 on the same B cell, just as the interaction of CD95L and CD95 on the same T cell appears to lead to T cell apoptosis in the CNS [19]. We also found that Bcl-2 expression appears to protect against B cell apoptosis in the CNS.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the present study we have shown that B cells expressing CD95 or CD95L in the CNS are much more vulnerable to apoptosis than B cells not expressing these proteins. This strongly suggests that B cell apoptosis in the CNS in EAE is mediated by the interaction of CD95L and CD95 on the same B cell, just as the interaction of CD95L and CD95 on the same T cell appears to lead to T cell apoptosis in the CNS [19]. We also found that Bcl-2 expression appears to protect against B cell apoptosis in the CNS.…”
Section: Discussionsupporting
confidence: 58%
“…We have previously shown that CD95+ T cells and CD95L+ T cells are particularly vulnerable to apoptosis in the CNS in EAE whereas Bcl-2+ T cells are relatively protected from apoptosis [19]. To determine whether apoptosis-regulating proteins play a similar role in B cell apoptosis, we analysed the expression of these proteins by CNS-infiltrating CD45RA/B+ cells 13 days after inoculation.…”
Section: Expression Of Apoptosis-regulating Proteins By B Cellsmentioning
confidence: 99%
“…Although we did not measure Fas expression on apoptotic T cells, Fas is known to be expressed on apoptotic T cells in GBM (Didenko et al, 2002). Our finding that T cells expressing Fas-L are much more likely to undergo apoptosis than T cells not expressing Fas-L is similar to what occurs in the CNS during spontaneous recovery from experimental autoimmune encephalomyelitis (White et al, 1998) and suggests that T-cell apoptosis in GBM is activation-induced and is occurring via the ligation of Fas by Fas-L on the same T cell. Apoptosis of T cells within GBM may explain, to a significant extent, the ineffectiveness of cell-mediated immunity towards gliomas.…”
Section: Discussionmentioning
confidence: 67%
“…However, in another study we have found that Ab cross-linking of Fas on human astrocytes can induce inflammatory chemokine and cytokine expression at both the mRNA and protein levels (C. Choi, X. Xu, J. W. Oh, S. J. Lee, and E. N. Benveniste, manuscript in preparation). To date, CNS-infiltrating activated T cells, microglia, and astrocytes have been reported to express FasL (16,68,69). However, it is not clear which cell type(s) contributes to the ongoing inflammatory response by engaging Fas on astrocytes in vivo.…”
Section: Discussionmentioning
confidence: 99%